The seed is the heart of the plant : Educational contets as powerful activators of the relationship between natural and digital - Buonanno, Rosa; Barbara Donnici, Maria (Rethinking childhood II: child and space, 2026)
The aim of this work is to explore the educational environment as a place resonating with harmony, beauty, and curiosity, where the different proposed activities allow natural learning processes in a multisensory and interactive flow. The vast existing literature confirms the interdependence among living beings, animals, and the vegetable world, and the importance of this interdependence for human beings. Plants—both in their behaviours, analysed by neurobiology, and in the psychophysical well-being they transmit—play a crucial role in understanding vital processes. This article analyses what emerged from children’s explorations of the dialog between plants and digital tools. The research adopts a qualitative approach based on pedagogical documentation which keeps track of interpretative processes of children and teachers, continuously reflecting on their learning through different languages: writing, graphics, images, texts, stories, videos. The results show how children understand, supported by digital tools, the vital processes of plants and the similarities between living beings. This paper would like to activate new areas of investigation on plants’ slow growing processes and the role of the educator–space relationship, creating opportunities to deepen ecological themes within Italian school curricula.